Boomer goes to school - McGeorge, Constance W.; Whyte, Mary (San Francisco, CA : Chronicle Books, 1996)
Boomer the golden retriever accompanies his owner to school for show-and-tell.
Keywords: Show-and-tell presentations; Golden retriever; Dogs; Schools